Analisis Perilaku Deteksi Dini Stroke pada Pasien Hipertensi Peserta Prolanis di Puskesmas Sungai Besar Kota Banjarbaru - sri nuryati; Meggy Wulandari Kai (Politeknik Kementerian Kesehatan Banjarmasin, 2026)
Hypertension is a risk factor for stroke. One way to prevent stroke complications is to empower hypertensive patients to independently learn about early stroke detection through health education, so that there are changes in their knowledge, attitudes, and actions towards early stroke detection, which is expected to minimize the negative impact of stroke. The purpose of this study was to analyze the behavior of Early Stroke Detection in Hypertensive patients participating in Prolanis at Sungai Besar Community Health Center. The research design was a descriptive study with a Cross Sectional approach, with the population being all Hypertensive patients participating in Prolanis at Sungai Besar Community Health Center, Banjarbaru City. A sample of 30 people was taken during April 2025 using the Accidental Sampling technique. To analyze the behavior of Early Stroke Detection in hypertensive patients, there are three domains measured, namely knowledge, attitudes, and actions of hypertensive patients, which were measured using a questionnaire, and processed descriptively. Based on the 3 (three) behavioral domains, it can be concluded that although the level of knowledge of Early Stroke Detection is still lacking, it is supported by the dominance of positive attitudes and actions, encouraging the majority of Hypertensive patients to have good